The role of athletic trainers in caring for athletes with feeding and eating disorders - Patel, S. R.; Winkelmann, Z. K.; Torres-McGehee, T. M. (Translational Journal of the American College of Sports Medicine, 2024)
Feeding and eating disorders and disordered eating behaviors are common in athletes; however, there are marked differences in the conditions. The Diagnostic Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) classifies feeding and eating disorders, whereas disordered eating is any problematic or abnormal eating habits that do not meet the criteria for a feeding and eating disorder by DSM-5 (1-3). Examples of eating disorders include anorexia nervosa, bulimia nervosa, and binge eating disorder. Feeding and eating characteristics such as excessive exercise, obsessions with thoughts of food and eating, and restricting, binging, and purging occur regularly. By contrast, disordered eating habits do not preoccupy the patient`s everyday life, and pathogenic behaviors do not happen regularly (1). Disordered eating behaviors are more common than eating disorders, and both conditions are more common in athletes than the general population and affect both male and female athletes (4).